"Animals are friends, not food": Anthropomorphism leads to less favorable attitudes toward meat consumption by inducing feelings of anticipatory guilt. (1st July 2019) - Wang, Feiyang; Basso, Frédéric
Abstract: Why do people befriend animals, yet don't feel conflicted about eating some of them? Previous research on the "meat paradox" suggests that the dehumanization of meat animals plays a crucial role in attenuating the negative affective states that consumers may experience when consuming meat. However, relatively little is known about how the converse process, namely anthropomorphism, influences meat consumption. The current research provides evidence that anthropomorphizing meat animals through the friendship metaphor, "animals are friends", can alter (omnivorous) consumers' attitudes and behavioral intentions toward meat eating, and induce feelings of guilt. More specifically, our experimental findings reveal that anthropomorphism has a negative effect on consumers' attitudes toward the food served in a restaurant and their intentions to patronize it when (pork) meat is on offer. This effect holds whether consumers are invited to consider themselves (Study 1a) or staff members (Study 1b) as taking part in a friendly human-animal interaction. We also demonstrate a similar effect of anthropomorphism on attitudes toward a (pork) meat product and their intentions to buy it, when consumers consider animal-animal friendship or human-animal friendship (Study 2). Last, we show that the negative effect of anthropomorphism on consumers' attitudes and behavioral intentions toward (pork) meat consumption is mediated by increased feelings of anticipatory guilt (Studies 3a and 3c). Nevertheless, no such effect was found with another kind of meat (beef), which indicates that anthropomorphizing meat animals through the friendship metaphor cannot be successfully applied to all commonly eaten species (Study 3b). Implications of these results for meat consumption are discussed.